Research collaboration agreement between Universiti Teknologi MARA (Malaysia) and Faculty of Economics and Business Universitas Pembangunan Nasional "Veteren" Jakarta (Indonesia) on tax avoidance and ownership structure in Malaysia and Indonesia - Nawi, Abdol Samad; Arieftiara, Dianwicaksih (2023)
This research collaboration agreement (hereinafter referred to as Agreement) made on 15th day of February 2023 between Universiti Teknologi MARA (hereinafter referred to as "UiTM") is a public university established under the Universiti Teknologi MARA Act 1976 [Act 173] whose address is at Chancellery, Universiti Teknologi MARA,40450 Shah Alam, Selangor, Malaysia and shall include its lawful representatives and permitted assigns and Faculty of Economics and Business Universitas Pembangunan Nasional "Veteren" Jakarta (hereinafter referred to as "FEB UPNJV"), a higher education institution under the Indonesian Ministry of Education is located at Jalan RS. Fatmawati No. 1, Pondok Labu, South Jakarta 12450, Indonesia and including its authorized representatives and permitted transfers from other parts.